Au cœur de la guerre du Việt Nam : herbicides, napalm et bulldozers contre les montagnes d’A Lưới - Amélie Robert (Revue de Géographie Alpine)
In the western part of the Thừa Thiên Huế province in Central Vietnam, the A Lưới Mountains were strongly affected by the Vietnam War (1961-1975). They were a refuge area for the Việt Cộng and crossed by the Hồ Chí Minh trail, which served as a strategic axis for them. Numerous herbicide sprayings and bombings, including napalm, struck the mountains and had a greater intensity than was the case in other landscape units. The US-South Vietnamese troops, which committed these practices, conducted a war against the enemy’s environment. But the enemy was also responsible for damage in this regard. In particular, the Việt Cộng used bulldozers to construct several routes on the Hồ Chí Minh trail. Maps of the land used around 1954 and in 1975 were drawn along transects; a comparison between them shows the landscape dynamics that occurred during the war. Some sylvosystems of the mountain area of A Lưới regressed, especially in the main valley. But as an indirect consequence of the war, others made progress. Because of the fighting, mountain-dwellers belonging to minority ethnic groups changed their practices and then left the area, thus leading to forest recovery on the disused land. For the Kinh, the ethnic majority group, the war was an opportunity to become more familiar with the mountain area that they had previously neglected.